Obesity and outpatient rehabilitation using mobile technologies: the potential mHealth approach - Castelnuovo, Gianluca; Manzoni, Gian Mauro; Pietrabissa, Giada; Corti, Stefania; Giusti, Emanuele Maria; Molinari, Enrico; Simpson, Susan (Frontiers in Psychology, 2014)
Obesity is currently an important public health problem of epidemic proportions (globesity). Inpatient rehabilitation interventions that aim at improving weight-loss, reducing obesity-related complications and changing dysfunctional behaviors, should ideally be carried out in a multidisciplinary context with a clinical team composed of psychologists, dieticians, psychiatrists, endocrinologists, nutritionists, physiotherapists, etc. Long-term outpatient multidisciplinary treatments are likely to constitute an essential aspect of rehabilitation. Internet-based technologies can improve long-term obesity rehabilitation within a collaborative approach by enhancing the steps specified by psychological and medical treatment protocols. These outcomes may be augmented further by the mHealth approach, through creating new treatment delivery methods to increase compliance and engagement. mHealth (m-health, mobile health) can be defined as the practice of medicine and public health, supported by mobile communication devices for health services and information. mHealth applications which can be implemented in weight loss protocols and obesity rehabilitation are discussed, taking into account future research directions in this promising area.